Racial and ethnic characteristics and cancer-specific survival in Primary Malignant Cardiac Tumors - Aloysius, Mark M.; Shrivastava, Sanskriti; Rojulpote, Chaitanya; Naseer, Raza; Hanif, Hamza; Babic, Milos; Gentilezza, Kenneth; Boruah, Pranjal K.; Pancholy, Samir (Frontiers in Cardiovascular Medicine, 2022)
Background: There is limited insight into the epidemiological characteristics and effect of race and ethnicity on Primary Malignant Cardiac Tumors (PMCTs). Objectives: Comparison of clinical characteristics and cancer-specific survival outcomes of major races in the United States form the SEER registry. Methods: ICD-O-3 codes were used to identify PMCTs for the years 1975 to 2015. Three major races were identified -“White”, “Black” and “Asian/Pacific Islander”. Cancer-specific survival outcomes were compared using Kaplan-Meier analysis across and amongst races, based on tumor histology. A subgroup analysis of cancer-specific survival was performed between “Hispanics” and “non-Hispanics.” Results: 720 patients were identified- 47% females and 79% White, mean age at diagnosis (47±20 years). Black patients were significantly younger (39±18 years) and presented more commonly with angiosarcomas (53%). Non-angiogenic sarcomas and lymphomas were the most common tumors in the White (38%) and Asian/Pacific Islander (34%) cohorts. For a median follow-up period of 50 (IQR3-86) months, cancer-specific survival (mean± SD, in months) was worse in Blacks (9±3) as compared to Whites (15±1) and Asians/Pacific Islanders (14±1). [p value; Black vs White <0.001; Black vs Asian/Pacific Islanders=0.017, White vs Asian/Pacific Islanders= 0.3]. Subgroup analysis with 116 (16%) Hispanics (40% females; mean age of 40 ±20 years) showed a longer mean cancer-specific survival of 16.9±2.4 months as compared to 13.6 ±1.1 months in non-Hispanics. (p=0.011) Conclusion: Black and non-Hispanic patients have poorer cancer-specific survival in PMCTs.